The first grader [videorecording (DVD)] - Chadwick, Justin; Feuer, Sam, 1974-; Feuer, Sam, 1974-; Harris, Naomie, 1976-; Litondo, Oliver; Kgoroge, Tony (NGHT, LLC. ; distributed by Vivendi Entertainment, 2011)
A heartwarming and inspiring true story of an 84-year-old Kenyan villager and ex-Mau Mau freedom fighter who fights for his right to go to school for the first time to get the education he could never afford. It is a triumphant testimony to the transforming force of education.